KANDUNGAN INFORMASI INKREMENTAL MANAJEMEN LABA TERHADAP PROFITABILITAS MASA DEPAN: STUDI PADA PERUSAHAAN PUBLIK DI INDONESIA - Windu Mulyasari (Tirtayasa Ekonomika, 2016)
This study aimed to test the moderating influence of the investment opportunity set on the relationship between earnings management and future profitability. Earnings management indicates that it has predictive information content that influence on future profitability. This predictive content can be shown on the level of corporate profitability. The high level of earnings management that affect the level of profitability becomes low. The result of the test shows that the level of statistical significance, if their earnings management is high (low) affect the profitability of a low (high). This study also explored the effect of investment opportunity set when considered in the earnings management, can affect profitability. The test results support that if the investment opportunity set high (low) and high earnings management (low), then the profitability of the company to be low (high).Key word : earning managements, investment opportunity set, future profitability